الحفاظ على التراث المعماري في مصر القديمة - عبدالله، ماجدة أحمد (الاتحاد العام للآثاريين العرب, 2017)
مما لا شك فيه وكما يعلم الجميع كل ما تتعرض له أثار حضارات العالم القديم الآن، سواء من تخريب أو تدمير أو إهمال أو عبث أو سرقة وتهريب لخارج حدودها الجغرافية، تلك الآثار تركها لنا أجدادنا شامخة وعظيمة تدل على عظمة الإنسان الذي أبدع في صنعها، وتوضح مهارته الفائقة في البناء والتشييد وعظمة تفكيره في بناء حضارته. ومن المعروف أن الله قد أختص منطقة الشرق الأدنى القديم بعدة حضارات متجاورة جغرافيا، ومتزامنة أو متلاحقة زمنيا، تواصلت حضاريا في كثير من الأحيان، وتصارعت في أحيان أخرى. ومن الملاحظ ما وصلت إليه حال الآثار المصرية القديمة والتي تمثل تراثا معماريا كبيرا تركه لنا المصري القديم كإرث حضاري شاهد على عظمة وقوة تلك الحضارة المصرية، ونلمس ذلك في إهمال ترميمها أو سرقتها، أو الإساءة إليها بتحطيمها وبعثرتها. ومن المؤكد علميا أن المصري القديم قد أدرك عظمة ما تركه الآباء والأجداد له، ولذلك وضع الملوك القدماء على عاتقهم مهمة ترميم الآثار وإعادة رونقها المعماري، في حال إذا لحق بها أي تدمير أو تخريب إما بسبب طبيعي مثل عوامل التعرية وما شابه، أو لتدخل عنصر بشري غازي لمصر مثل الهكسوس، أو لتعرضها في أزمنة ضعف حكام البلاد للسرقة والنهب، ونستدل على حرص المصري القديم على ترميم أثاره من عدة نصوص مصرية قديمة، ومن بينهم على سبيل المثال لا الحصر نصوص تدلل على حرص الملكة حتشبسوت (1472- 1457 ق.م)، والملك تحوتمس الثالث (1479- 1424 ق.م)، والملك أمنحتب الثالث (1388- 1348 ق.م) والملك رعمسيس الثاني (1279- 1212 ق.م) وغيرهم كثير. حول هذا الموضوع الهام سنوضح التعبيرات الدالة على الترميم، وسائل الترميم في مصر القديمة، كيفية أعادة أرث الأجداد ومبانيهم إلى ما كانت عليه وذلك من خلال دراسة تحليلية للنصوص المصرية القديمة.
Undoubtedly, everyone knows what happens to our civilizations today, its destruction, negligence or scatters, sometimes; it has been stealing to sale outside its geographical boundaries. These civilizations bequeathed to us by our ancestors, it shows their greatness and how they were excelled in buildings, it shows their skill in the construction as well. God has favored our land in Near East with several ancient civilizations, it was contiguous geographically, and sometimes those civilizations were conflicted or communicated together. It is remarkable what we have reached by our ancient Egyptian antiquities, which represents a significant architectural heritage left to us as a legacy of the ancient Egyptian, it indicate their civilized thought, it has witness to the greatness and strength of those Egyptian, and we see now how it has been neglect restored or stolen, or scatters on the ground. Certainly the ancient Egyptian has realized the greatness of their Heritage which their parents and grandparents leaved to them; the ancient Egyptian kings have put their planes to make the restoration of their great monuments, to return its architectural glory, in case it has destroyed by any destruction natural, or by human such as the Hyksos. I assured that, ancient Egyptian concerned with restoration and that is clear at several ancient Egyptian texts, for example, as we see in the time of, Queen Hatshepsut (1472-1457 B.C), King Thutmose III (1479-1424 B.C), King Amenhotep III (1388-1348 B.C) and King Rameses II (1279-1212 B.C) beside many others different periods. On this important topic, I will explain the words which indicate "the restoration" in ancient Egyptian texts, and I will declare how they had restored their ancient different buildings in Egypt, and how they reserved their legacy to us, I will researches this idea through an analytical study of ancient Egyptian texts.
Keywords: التراث المعماري -- مصر القديمة -- الترميم المعماري -- النصوص المصرية